Tinjauan Pertimbangan Hakim Mahkamah Agung Atas Perkara Illegal Fishing - Andhini, Lastika Wahyu; -, Kristiyadi, S,H., M.Hum (Sebelas Maret University, 2019)
Legal research aims to fnd out the reason of Cassation fling compliance by the public prosecutor in the case illegal fshing with the provision of article 253 KUHAP as well as fnd out the suitability of the consideration of the Supreme Court granted the petition for cassation and Decides the defendant is proven legally and convincingly guilty of fshing boats without operationalize offcial documents was in accordance with clause 256 jo 193 Article paragraph (1) of the KUHAP. This research included in this type of normative legal research that is both prescriptive and applied. Use primary and secondary legal materials. The research approach with case studies. Legal materials collection technique is done by collecting documents for the study of law. Legal materials analysis techniques of deductive syllogisms that are done in a stemmed from the fling of the major premise then fled a minor premise, from the second premise obtained then it can be drawn conclusions with regard to the matter. The results obtained from this research about the Supreme Court verdict Number 1727 K/Pid. Sus/2014 were in accordance with the provisions contained in Article 253 KUHAP especially clearly listed on the letter a that determines whether a true rule of law not applied or not applied as it should be. Article 256 jo 193 Article paragraph (1) of the KUHAP contains if the Court held that the defendant was guilty of a criminal offence who didakwakan him, then the Court dropped the criminal. Legal considerations the Tribunal Judges in examining the petition for Cassation Prosecutor granted; the High Court ruling cancelling the feld number: 129/PID/2013/PT. PDG 25 July 2013 has been improving and the verdict of the District Court the feld Number: 254/Pid. B/2013/PN. PDG on 30 may 2013.Keywords: Illegal Fishing, IUU Fishing, The Submission, Consideration Of Cassation Judge, Ship Catching Fish, Fishing